1993
DOI: 10.1111/j.1399-3054.1993.tb05285.x
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal variations of amino acids and organic acids in xylem fluid from Lagerstroemia indica: an endogenous circadian rhythm

Abstract: Diurnal variations in the concentrations of major organic compounds occurred in xylem fluid extracted from Lagerstroemia indica L. The concentration of amino acids and the N/C ratio was at a maximum and that of organic acids was at a minimum between 1230 and 2030 h. Since the concentrations of total organic nitrogen, total amino acids and most individual amino acids (but not organic acids or sugars) were also proportional to xylem tension two experiments were performed to discern whether variations in chemistr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 27 publications
1
21
0
Order By: Relevance
“…The dynamic nature of nutrient transport in the xylem has been demonstrated previously by both techniques that allow sampling of xylem sap from intact, transpiring plants [root pressure chamber:, e.g. Schurr & Schulze (1995); xylem‐tapping insects: Andersen & Brodbeck (1989), Andersen, Brodbeck & Mizell (1993), (1995)]. A number of processes has been suggested that cause the diurnal variation of xylem sap composition (Schurr 1998b), that range from variation of nutrient availability at the root system, nutrient uptake, variable dilution by the transpiration rate to lateral exchange along the xylem with parenchyma and/or phloem.…”
Section: Introductionmentioning
confidence: 96%
“…The dynamic nature of nutrient transport in the xylem has been demonstrated previously by both techniques that allow sampling of xylem sap from intact, transpiring plants [root pressure chamber:, e.g. Schurr & Schulze (1995); xylem‐tapping insects: Andersen & Brodbeck (1989), Andersen, Brodbeck & Mizell (1993), (1995)]. A number of processes has been suggested that cause the diurnal variation of xylem sap composition (Schurr 1998b), that range from variation of nutrient availability at the root system, nutrient uptake, variable dilution by the transpiration rate to lateral exchange along the xylem with parenchyma and/or phloem.…”
Section: Introductionmentioning
confidence: 96%
“…The free amino acids found in the sap of plants are the base diet of the leafhoppers feeding on the xylem or plant phloem, which determines the selection of the primary host plants and dispersion of leafhoppers in different habitats and times of the year (Russel et al 1987, Andersen et al 1993. For species Homalodisca coagulata the selection of host plants and the adult population were verified to be positively correlated with the concentration of a few amino acids found in standard plants regarding feeding, and the nymphs failed to develop successfully on the hosts preferred by the adults due to the fact that they cannot assimilate as efficiently as the adults the essential nutrients in nutritionally unbalanced plants (Brodbeck et al 1990;1995).…”
Section: Introductionmentioning
confidence: 99%
“…Adults of the glassywinged sharpshooter, Homalodisca coagulata (Say) for example, tend to select host plants with higher concentrations of certain nutrients in the xylem sap (Brodbeck et al 1990). The nutritional quality of xylem sap can vary considerably in plants depending on several environmental factors, such as soil fertility and humidity, shade, plant age and location, etc (Andersen et al 1993, Andersen & Brodbeck 1991. This behavior could explain the aggregated pattern observed for Acrogonia sp.…”
Section: Resultsmentioning
confidence: 99%